Molecular characterization uncovering a novel genus of tapering-filamentous cyanobacteria from Thailand: Phayaothrix lacustris gen. & sp. nov. (Nostocales, Cyanophyta) - Tawong, Wittaya; Nishimura, Tomohiro; Pongcharoen, Pongsanat; Saijuntha, Weerachai; Kucharoenphaibul, Siriwat; Sunpapao, Pathipat; Pongpadung, Piyawat; Ponza, Supat (Phytotaxa, 2024)
In this study, novel Calothrix-like strains NUACC09 and NUACC10 were isolated from the surfaces of rocks in Phayao Lake, Thailand. Morphological, molecular and ecological comparisons were investigated to characterize the taxonomic status of these novel strains. Under the light microscope, morphological studies indicated that these two strains were morphologically similar to Calothrix but could be differentiated by production of a non-hyaline hair at the terminal end, a low degree of tapering, twisted or loop-forming filaments, a knotted growth form, intertwined trichomes and presenting more than one trichome within the single sheath. In the 16S rRNA and rbcLX gene phylogenetic tree analyses, our strains formed a monophyletic clade with former freshwater/terrestrial Calothrix-like taxa separating distantly from other Calothrix-like genera. Furthermore, low 16S rRNA gene sequence similarity (<94.9%) to the closely related genera and species delimitation analyses (PTP/bPTP, GMYC, ABGD and ASAP methods) indicated that this clade should be considered as a different cyanobacterial lineage. The phylogenetic tree and secondary structures (D1–D1′, V2, Box-B and V3 helix) based on 16S–23S rRNA ITS regions suggested that multiple species might be contained in this clade. Therefore, here, Phayaothrix was proposed as a novel cyanobacterial genus with Phayaothrix lacustris sp. nov. as the type species following the International Code of Nomenclature for algae, fungi and plants.